Evidence that the presence of psychosis in non-psychotic disorder is environment-dependent and mediated by severity of non-psychotic psychopathology. Issue 11 (August 2015) - Guloksuz, S.; van Nierop, M.; Lieb, R.; van Winkel, R.; Wittchen, H.-U.; van Os, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Evidence suggests that in affective, non-psychotic disorders: (i) environmental exposures increase risk of subthreshold psychotic experiences (PEs) and strengthen connectivity between domains of affective and subthreshold psychotic psychopathology; and (ii) PEs are a marker of illness severity. Method In 3021 adolescents from the Early Developmental Stages of Psychopathology cohort, we tested whether the association between PEs and presence of DSM-IV mood disorder (MD)/obsessive–compulsive disorder (OCD) would be moderated by risk factors for psychosis (cannabis use, childhood trauma and urbanicity), using the interaction contrast ratio (ICR) method. Furthermore, we analysed whether the interaction between environment and PEs was mediated by non-psychotic psychopathology. Results The association between PEs and MD/OCD was moderated by urbanicity (ICR = 2.46, p = 0.005), cannabis use (ICR = 3.76, p = 0.010) and, suggestively, trauma (ICR = 1.91, p = 0.063). Exposure to more than one environmental risk factor increased the likelihood of co-expression of PEs in a dose–response fashion. Moderating effects of environmental exposures were largely mediated by the severity of general non-psychotic psychopathology (percentage explained 56–68%, all p < 0.001). Within individuals with MD/OCD, the association between PEs and help-seeking behaviour, as an index of severity, was moderated by trauma (ICR = 1.87, p = 0.009) and urbanicity (ICR = 1.48, p = 0.005), but not by cannabis use. Conclusions In non-psychotic disorder, environmental factors increase the likelihood of psychosis admixture and help-seeking behaviour through an increase in general psychopathology. The findings are compatible with a relational model of psychopathology in which more severe clinical states are the result of environment-induced disturbances spreading through a psychopathology network.